2008
DOI: 10.1210/en.2007-1650
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ghrelin as a Therapeutic Approach for Age-Related Physiological Changes

Abstract: Aging is associated with decreases in food intake and GH secretion, termed the anorexia of aging and somatopause, respectively. The mechanisms underlying these phenomena are not fully understood. Although many approaches have attempted to improve these age-related physiological changes, none have achieved satisfactory results. Ghrelin, a 28-amino-acid acylated peptide, was identified as an endogenous ligand for the GH secretagogue receptor. Ghrelin stimulates GH secretion and food intake in animals and humans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Also, the plasma acylated ghrelin concentration was shown to be significantly increased after rikkunshito treatment [15]. Ghrelin stimulates food intake [9] and triggers a positive energy balance through a central mechanism involving hypothalamic neuropeptides [9][10][11][12]. Taken together, these reports suggest that the induction of ghrelin could be In the present study, however, the administration of rikkunshito did not increase the ghrelin concentration per se.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Also, the plasma acylated ghrelin concentration was shown to be significantly increased after rikkunshito treatment [15]. Ghrelin stimulates food intake [9] and triggers a positive energy balance through a central mechanism involving hypothalamic neuropeptides [9][10][11][12]. Taken together, these reports suggest that the induction of ghrelin could be In the present study, however, the administration of rikkunshito did not increase the ghrelin concentration per se.…”
Section: Discussioncontrasting
confidence: 41%
“…During metabolic processing, a fraction of desacyl-ghrelin is acylated in position 3 (serine) to form variants of acyl-ghrelin. Acyl-ghrelin displays dosedependent GH-releasing activity [8,9], stimulates food intake, triggers a positive energy balance [10][11][12], and is considered to be the active form of ghrelin [11,[35][36][37]. Actually, several components of rikkunshito demonstrate inhibitory activity against ghrelin desacylating enzymes [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ghrelin decreases energy expenditure in rodents, thus increasing adiposity and facilitating weight gain (Tschop et al, 2000). Ghrelin concentrations have been reported to be decreased in elderly people (Rigamonti et al, 2002;Sturm et al, 2003), and old rats failed to upregulate the levels of circulating ghrelin during food deprivation (Wolden-Hanson et al, 2004), indicating that inadequate ghrelin response might contribute to the anorexia of aging (Kmiec, 2010 endogenous ghrelin significantly contributes to the regulation of food intake in humans (Lippl et al, 2012), exogenous administration of ghrelin or its receptor agonists has been suggested as a potential therapeutic approach for anorexia and other age-related physiological changes (Ariyasu et al, 2008;Muccioli et al, 2002). Moreover, this approach has also been considered in the treatment of cachexia associated with chronic illnesses, including cancer, heart failure, chronic kidney disease, and acquired immunodeficiency syndrome (DeBoer, 2008;Deboer et al, 2008;DeBoer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies highlight the possible therapeutic effects of these molecules in diseases associated with muscle wasting, including anorexia nervosa, chronic obstructive pulmonary disease (COPD), functional dyspepsia and chronic heart failure (4 -6), despite the necessity to assess the long-term efficacy and safety of GHSs therapies. Furthermore, the use of GHSs has been proposed to either prevent or treat the effects of aging and disuse on skeletal muscles (7)(8)(9)(10).…”
mentioning
confidence: 99%